Real-world sex differences in healthcare utilization after cryoballoon ablation: 2-year outcomes from the Cryo Global Registry - Khelae, Surinder Kaur; Chun, Kyoung Ryul Julian; Drephal, Christian; Scazzuso, Fernando; Kueffer, Fred J.; van Bragt, Kelly A.; Lawrenz, Thorsten; Todd, Derick; Ptaszyński, Paweł; Földesi, Csaba (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCryoballoon ablation (CBA) is a well-established treatment for atrial fibrillation (AF). However, evidence on the impact of sex on outcome is sparse. This real-world analysis aims to describe outcome after CBA in both sexes.MethodsThis registry is an ongoing, global evaluation of CBA procedures in standard-of-care practice. Females undergoing CBA were compared to males at baseline and 12-, and 24-months post-ablation. Serious procedure-related adverse event rate, rate of atrial arrhythmia (AA) recurrence, repeat ablation, hospitalization, cardioversion, and quality-of-life (QoL; EQ-5D-3l) were compared.ResultsOf 3,089 patients with 12-month follow-up, 1,136 (36.8%) were female; and a subset of 1,099 patients (400 female) were followed through 24 months. Females presented with different comorbidities at baseline. The complication rate was low overall in females (3.9%) and males (2.7%, p = 0.07). At 24-month follow-up, the rate of AA recurrence was 25.0% in females and 22.1% in males and female sex was a predictor of AA recurrence (HR adj = 1.21, p = 0.047) and rehospitalizations (HR adj = 1.25, p = 0.03) in a propensity score adjusted analysis. In addition, females stayed in the hospital longer compared to males during the index ablation procedure (47.9% with 2 or more days in hospital vs. 39.3% in males, p < 0.01), as well as during the first hospital stay post-ablation (78.2% with 2 or more days in hospital vs. 60.2% in males, p < 0.01). QoL improved from baseline to 12 months in females (0.85 ± 0.15–0.90 ± 0.13) and males (0.91 ± 0.13–0.94 ± 0.11) and remained high at 24 months.DiscussionCBA performed according to standard-of-care practice was safe in both sexes. The efficacy of CBA is marginally lower in females, but 75% of females remained free from AA recurrence at 24-months and reported a meaningful improvement in QoL post ablation. Systematic Review Registrationhttps://clinicaltrials.gov/ct2/show/NCT02752737, The Cryo Global Registry (NCT02752737)